Development And Validation Of Guidance Module For Children In Prison: A Study At Kajang Women's Prison, Malaysia - Jawiah Dakir; Rosilawati Mohd. Hanapi; F. Sham; Hj Tibek Siti Rugayah; Badzis Mastura; Mohd Awal Noor Aziah; Muhammad Hilmi Jalil; Siti Maheran Ismail Ibrahim (Sakarya University, 2024)
Indexed by SCOPUS